Pengaruh Corporate Social Responsibility terhadap Penghindaran Pajak dengan Kepemilikan Institusional sebagai Moderasi - Ridho Hamdani; Herlina Helmy (Universitas Negeri Padang, 2023)
This study examines the effect of corporate social responsibility on tax avoidance with institutional ownership as a moderating variable. This research is a type of causative research. The population in this study is the manufacturing industry sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The research sample was obtained using purposive sampling method which produced 138 observations. The results of this study explain that Corporate Social Responsibility has no significant effect on tax avoidance practices. And institutional ownership cannot moderate or weaken the relationship between Corporate Social Responsibility and tax avoidance. Subsequent research, added other independent variables and added the research time span so that it would provide better results.